Effect of Different Mouthwashes on Gingival Health of Dental Students - Reaam A. Fadhil; Saher S.Gasgoos (University of Mosul, College of Dentistry, 2021)
Aims: To evaluate and compare the effectiveness of different mouthwashes in decreasing the gingival inflammation. Materials and Methods: The participants were (88) dental students, aged between 18 to 25 years (44 males and 44 females). The students with mild to moderate gingivitis were randomly divided into four groups, 22 Participants for each one. In Group A, participants were advised kin gingival mouthwash, Group B participants used Wisdom daily gum health mouthwashes, Group C participants are given LA-CALUT aktiv mouthwashes, and KIN B5Gums mouthwash was given to Group D. The students were ad-vised to use 10 ml of given mouthwash for 30 seconds, twice a day, not immediately after tooth brushing (at least 5minutes after tooth brushing), for 14 days. The parameter was recorded for gingival index (GI) at 0 and 14 days. Results: The reduction in the gingival inflammation is highly significant on day 14 (T1) com-pared to baseline values (T 0). There are highly significant differences among the four types of mouthwashes used for the reduction of gingival inflammation. These results prove that the four mouthwashes used have variable efficiency on gingival inflammation depending on their major active chemical components. Mouthwash C is the most effective one in reducing gingival inflammation. Mouthwash A, mouthwash B and mouthwash D have no significant differences between them. Conclusions: In this study, all the mouthwashes were used showed clinical efficacy in reducing gingival inflammation. The mouthwash LACALUT aktiv is the most effective one.